The Microbiota-gut-brain axis in vascular cognitive impairment: unraveling the mysterious link and therapeutic prospects - Liu, Tingting; Li, Ying; Xiong, Xuejiao; Lai, Xinxing; Xu, Xiangqing (Frontiers in Immunology, 2025)
BackgroundVascular cognitive impairment (VCI) exhibits particularly high prevalence in East Asian populations. However, its pathogenesis remains elusive due to its multifactorial and complex nature. Emerging evidence highlights the microbiota-gut-brain axis as a novel and promising paradigm for elucidating VCI mechanisms and developing therapeutic interventions. This systematic review aims to synthesize recent advances in this field, offering critical perspectives to guide future research on VCI through the lens of gut-brain interactions. Notably, given Traditional Chinese Medicine’s (TCM) holistic and multi-target therapeutic advantages, we incorporate TCM studies to complement conventional approaches.MethodsWe systematically searched PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP), and Wanfang database for relevant studies from their inception to March 31, 2025, and conducted a comprehensive review.ResultsA total of 22 relevant studies were included in the final review. Current research primarily focused on analyzing the altered gut microbiota in VCI patients, with findings indicating significant changes in both the structure and abundance of gut microbiota. Enterobacteriaceae exhibited potential as a diagnostic biomarker for post-stroke cognitive impairment (PSCI) (AUC=0.629), while distinct microbial signatures involving Bifidobacterium, Lactobacillus gasseri, and Anaerostipes hadrus may effectively differentiated PSCI patients from stroke survivors without cognitive deficits (AUC values of 0.785, 0.792, and 0.750, respectively). Furthermore, multiple interventional studies from both basic and clinical research systematically explored the microbiota-gut-brain axis as a promising therapeutic target for VCI. They evaluated the efficacy of diverse approaches—such as fecal microbiota transplantation, aerobic exercise, pharmacological interventions, and acupuncture—on key outcome including gut microbiota composition, cognitive function, hippocampal integrity, and inflammatory markers. Basic experimental studies revealed that Prevotella histicola, Clostridium butyricum, aerobic exercise, and TCM improved cognitive function, whereas trimethylamine N-oxide exacerbated cognitive impairment. The efficacy of TCM was further confirmed by clinical studies.ConclusionResearch is in its early stages, but the microbiota-gut-brain axis already offers promising prospects for a deeper understanding and discovery of potential new therapeutic targets for VCI.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024560293.